2019
DOI: 10.1016/j.jamda.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Dynapenia (Muscle Weakness) and Low Vitamin D Status on Incident Disability

Abstract: Dynapenia only and dynapenia combined with low 25 (OH) D serum levels were important risk factors for ADL disability in middle-aged individuals and older adults in 2 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Vitamin D receptor (VDR) is expressed in different human tissues, which strengthens the hypothesis that VitD acts beyond its classical function of bone metabolism and calcium homeostasis, playing an important role in various systems [5]. In the central nervous system, for example, vitD seems to be associated…”
Section: Introductionsupporting
confidence: 54%
“…Vitamin D receptor (VDR) is expressed in different human tissues, which strengthens the hypothesis that VitD acts beyond its classical function of bone metabolism and calcium homeostasis, playing an important role in various systems [5]. In the central nervous system, for example, vitD seems to be associated…”
Section: Introductionsupporting
confidence: 54%
“…The variations in prevalence depend on the cut-off value, age, geographic location, and ethnicity of the population under study. 30,31 The prevalence of dynapenia in our study population was observed to be 31.3%, so it is within the middle range. In the present study, age and adiposity were significantly associated with a higher risk of dynapenia and interestingly, we found that women with a higher femoral neck T-score were less likely to have dynapenia.…”
Section: Dynapenia In Postmenopausal Womenmentioning
confidence: 57%
“…The season of the year in which blood was collected for the determination of serum 25(OH)D was recorded and used as a control variable: spring (March–May), summer (June–August), autumn (September–November), and winter (December–February) ( 38 ). Vitamin D supplementation and the use of carbamazepine [an anticonvulsant medication with the potential to reduce serum 25(OH)D concentrations] were also used as control variables ( 39 ).…”
Section: Methodsmentioning
confidence: 99%